(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Cardiovascular disease (CVD) is one of the leading causes of death and morbidity as well as imposing a huge economic burden at both country and household level. Upto 90% cardiovascular disease may be preventable if established risk factors are avoided. In this context, dietary nitrate from vegetables was highlighted as a potential candidate for cardio protection. Hence, by supplying dietary nitrate and other bio-active compounds to ease the risk of cardiovascular disease, present research work was carried out. Among the tested vegetables, the highest nitrate content (745 mg/100g) was determined in Indian spinach. In addition, Indian spinach also possesses more chlorophyll (150mg/100g), beta carotene (40mg/100g) and lycopene (34mg/100g) than other tested vegetables in the current study. In case of anti-oxidant content, Indian spinach showed the highest (103mg/100g) vitamin C content. Taken all together, Indian spinach may be a good and cheapest source of cardio protective molecule (nitrate) bioactive compounds to avoid risk of cardiovascular disease. J. Bangladesh Agril. Univ. 16(1): 82-87, April 2018